Comparing Lecture and Discussion Methods: Assessment of Perception of Medical Laboratory Science Students at Sultan Abdurrahman School of Health Technology Gwadabawa, Nigeria - Miya, Yusuf Yahaya; Yusuf, Anas (Darul Yasin Al Sys, 2024)
Medical Laboratory Science skilled workers are needed at hospital and other settings more than ever. These workers are produced by schools through teaching and learning. Medical Laboratory scholars are on many occasions involved in training and teaching. Nevertheless, nowadays teaching is been centered towards the views of learners, thus the aim of those study was to compare lecture and discussion teaching methods among students at Medical Laboratory Science Department at Sultan Abdurrahman School of Health Technology Gwadabawa with a view to select better learning method. A survey of 60 participants using a semi-structured questionnaire was done and descriptive statistics aided the analysis. Best teaching method selected by the respondents was the lecture method (100.0%); while none of them (0.0%) submitted discussion method as the method they want in learning Medical Laboratory Science. Advantages or reasons for choosing lecture method than the discussion method as submitted by the respondents are stated. The most frequently stated was